How Do Employees Understand Negative Leadership? The Non-linear Relationship Between Abusive Supervision and Employee Innovation Behavior: Job Performance as a Moderator - Yuan, Kuo-Shu; Ng, Tung; Wu, Tung-Ju (Frontiers in Psychology, 2022)
This study aims to investigate the non-linear relationship between abusive supervision and employee innovation behavior, and further examine how job performance moderates these relationships. Two hundred and seventy-six employees across three industries (restaurant service, tourism, and financial service) in China participated in this study and completed the survey at two-time points. The results of curve regression show as follows: 1) There exists a non-linear relationship between abusive supervision and innovation behavior. 2) job performance moderates the non-linear relationship between abusive supervision and employee innovation behavior. For employees who perform well at work, there exists a U-shaped relationship between abusive supervision and innovative behavior. Whereas, for employees with poor job performance, when abusive supervision reaches a certain level, it will promote employee innovation behavior; and the excess of abusive supervision will inhibit employee innovation behavior, showing an inverted U-shaped curve relationship. The finding suggests it is important for managers to understand the stakes arising from abusive supervision. That is, managers should manipulate the right level of abuse supervision to promote employee innovation behavior.